Impact of Demographical Factors and Language Acquisition Level on Depression Symptoms Among Arabic Language Learners - Maba, Aprezo Pardodi; Akla, Akla; Aminnuddin, Nur Amali (Indonesian Institute for Counseling, Education, and Therapy & Indonesian Counselor Association, 2022)
The prevalence of depression among language learners, specifically Arabic learners, should receive proper attention from academics. Unfortunately, it would be easily overlooked by scholars because they were tend more focusing on the development of effective teaching strategy. The objective of current study was to investigate the effect of demographic variables and language proficiency on symptoms of depression in individuals learning Arabic as a second language. This cross-sectional study involved 1126 participants who voluntarily provided their consent. Of the participants, 762 were female and 364 were male (age M = 20.03 and SD = 1.56). The study collected demographic information, assess language acquisition levels, and measure symptoms of depression. Data was analyzed using descriptive statistics, Pearson correlation, and multiple linear regression. Results showed that model proposed in this study with its predictors explained 7.5% of the variance in depression symptoms while factors such as sex, number of siblings, living arrangement, listening skills, and reading skills were found being significant predictors in the model. This study highlights the prevalence of depression among individuals learning Arabic as a second language and the importance of demographic variables and language proficiency in predicting depression symptoms. The findings suggest that interventions to address depression in this population should take into account factors such as sex, number of siblings, living arrangement, and language skills.